2017
DOI: 10.1186/s13028-017-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of low prevalence of mycobacterial lymphadenitis in wild boars (Sus scrofa) in Poland

Abstract: Mycobacterium spp. and Rhodococcus equi are generally regarded as the main causes of lymphadenitis in pigs and wild boars. In Poland, mycobacterial submandibular lymphadenitis was first diagnosed in a wild boar in 2012 but Mycobacterium spp. infections are also present in the Polish population of European bison (Bison bonasus). The prevalence of lymphadenitis in Polish wild boars has been found to 8.4% (95% CI 6.2–11.3%) and it has been proved that R. equi is not an important cause of purulent lesions in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In contrast, one of our more significant findings is that TB was identified in 21 of the 55 tested wild boar. The first confirmed TB case in a wild boar in the Bieszczady region was reported in 2012 (a single individual) [4]; before this time, no cases of TB had been detected [8,14]. The population density of wild boar was found to be 5-13 animals per 10 km 2 of forest in the period 2011-2017 (Forest Management Plan of the Stuposiany and Lutowiska Forest Inspectorate, 2015; Unpublished data, Stuposiany Forest Inspectorate).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one of our more significant findings is that TB was identified in 21 of the 55 tested wild boar. The first confirmed TB case in a wild boar in the Bieszczady region was reported in 2012 (a single individual) [4]; before this time, no cases of TB had been detected [8,14]. The population density of wild boar was found to be 5-13 animals per 10 km 2 of forest in the period 2011-2017 (Forest Management Plan of the Stuposiany and Lutowiska Forest Inspectorate, 2015; Unpublished data, Stuposiany Forest Inspectorate).…”
Section: Discussionmentioning
confidence: 99%
“…Wild animals play an important role in the epidemiology of infectious diseases as reservoirs of several zoonotic and nonzoonotic diseases [1] . It has been clearly shown that wild boars can act as reservoirs for a long list of zoonotic bacterial agents [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The 1% chlorhexidine decontamination and MOD9 culture protocol enabled the isolation of three non-tuberculous mycobacteria from five different wild boars with a prevalence of 5.05%, in the range of the previously reported 0% to 11.1% prevalence of non-tuberculous mycobacteria in wild boar faeces 10 . In the lymph nodes, prevalence is 16.8% in Spain 8 whereas no mycobacteria could be detected in lymph nodes in another study in Poland 32 the prevalence of mycobacteria in wild boar varies among wild boar population, density and environment. M. vaccae was initially cultivated from cows in Austria 33 and has previously been isolated in wild boars in Australia 9 .…”
Section: Discussionmentioning
confidence: 87%